The geology of porphyry-related mesothermal vein gold mineralisation north of Kainantu, Papua New Guinea - Leach TM; Thirnbeck M; Mori W; Sione T; Harry K; Digan K; Petrie P (The Australasian Institute of Mining and Metallurgy, 1994)
Gold and lesser copper mineralisation are associated with porphyry-related vein systems periph-eral to two separate inferred intrusive centres north of Kainantu, Papua New Guinea (PNG). The intersection of NW trending structures, formed parallel to the Markham Fault, with NE trending transfer structures localise porphyry intrusions, and control vein distrib-ution.The Arakompa veins intrude pre-existing fractures in Akuna granodiorite, located proximal to an inferred porphyry. These veins are characterised by early quartz and later pyrite-chalcopyrite. Gold mineralis-ation is associated with Bi-Te phases in the sulphide veining. At Maniape, en echelon gash veins occur within the imbricate portion of a regional structure. Maniape is a high level carbonate-base metal gold system formed distal to the same porphyry source as Z ?-;4 kmmna